Individual strategies in the rat gambling task are related to voluntary alcohol intake, but not sexual behavior, and can be modulated by naltrexone - Tjernström, Nikita; Roman, Erika (Frontiers in Psychiatry, 2022)
Gambling disorder (GD) is the first non-substance, or behavioral, addiction to be included in Substance Related and Addictive Disorders in DSM-5. Since gambling disorder is a younger phenomenon relative to alcohol and substance use disorders, little is known about potential unique features in GD and to what extent characteristics are shared with alcohol and substance use disorders. The rat Gambling Task (rGT) is used to study decision making in rats. This study aimed to identify individual differences in rGT strategies and explore the stability of these strategies over time. Moreover, motor impulsivity, sexual behavior and voluntary alcohol intake was examined in rats with different rGT strategies. Finally, the response to naltrexone on performance in rats with different rGT strategies was investigated. Male Lister Hooded rats (n = 40) underwent repeated testing in the rGT, repeated copulatory behavioral tests and a seven-week period of voluntary alcohol intake through a modified intermittent two-bottle free-choice paradigm. Lastly, rats were treated with naltrexone prior to testing in the rGT. The results revealed individual choice strategies in the rGT that were stable over time, even after multiple interruptions and other behavioral testing. The rats with a risky choice strategy displayed higher motor impulsivity and higher voluntary alcohol intake than the other groups. No difference in sexual behavior was found between the different rGT groups. Lastly, in all rats irrespectively of rGT strategy, treatment with naltrexone decreased number of completed trials and premature responses, and increased omissions, which indicates an overall lowered motivation. In conclusion, rats with risky rGT strategies had higher voluntary alcohol intake, but not elevated sexual behavior, indicating shared underlying mechanisms between rGT strategies and alcohol intake but not natural rewards in terms of sexual behavior. Finally, naltrexone treatment resulted in an overall lowered motivation in the rGT.